Clearing the Air on Pollutant Disruptions of the Gut–Brain Axis: Developmental Exposure to Benzo[a]pyrene Disturbs Zebrafish Behavior and the Gut Microbiome in Adults and Subsequent Generations - Alexandra Alexiev; Ebony Stretch; Kristin D. Kasschau; Lindsay B. Wilson; Lisa Truong; Robyn L. Tanguay; Thomas J. Sharpton (Toxics)
Developmental exposure to benzo[a]pyrene (BaP), a ubiquitous environmental pollutant, has been linked to various toxic effects, including multigenerational behavioral impairment. While the specific mechanisms driving BaP neurotoxicity are not fully understood, recent work highlights two important determinants of developmental BaP neurotoxicity: (1) the aryl hydrocarbon receptor (AHR), which induces host metabolism of BaP, and (2) the gut microbiome, which may interact with BaP to affect its metabolism, or be perturbed by BaP to disrupt the gut–brain axis. We utilized the zebrafish model to explore the role of AHR, the gut microbiome, and their interaction, on BaP-induced neurotoxicity. We tested (1) how developmental BaP exposure and AHR2 perturbation in zebrafish link to adult behavior, (2) how these variables associate with the structure and function of the adult zebrafish gut metagenome, and (3) whether these associations are multigenerational. Our findings reveal a reticulated axis of association between BaP exposure, developmental AHR2 expression, the zebrafish gut metagenome, and behavior. Results indicate that AHR2 is a key modulator of how BaP elicits neurotoxicity and microbiome dysbiosis. Additionally, this axis of association manifests generationally. These findings demonstrate the importance of studying pollutant–microbiome interactions and elucidate the role of specific host genes in neurotoxicity and dysbiosis.